AN ANALYSIS OF RACIAL DISCRIMINATION IN ‘’MAX HAVELAAR’’ MOVIE - Kale, Kristina; Sulistyo, Teguh; Purnawati, Maria (Jurnal Tinta, 2024)
The aim of the study is to find out the types of racial discrimination in the film Max Havelaar and to find out the causes of racial discrimination in the film Max Havelaar. The study used a descriptive qualitative design. Descriptive qualitative design is used to describe and explain what has been interpreted from the research object. The researchers conducted the research by watching the film "Max Havelaar" several times and used a dictionary to check the data, identify, classify and conclude the data, and other tools used note taking. The researchers processed the data in the form of a dialogue. The data analysis process included data reduction, data presentation, inference/verification and triangulation. The data collected was then verified by an expert validator. The findings of this study are; 1) There are four types of racial discrimination found in the Max Havelaar film, namely; verbal antagonism discrimination, physical attack discrimination, extermination discrimination, and the last one is segregation. 2) There are four causes of racial discrimination in Max Havelaar film, namely; internal racism, institutional racism, systemic racism and interpersonal racism. In conclusion, the researchers hope they can expand the racial discrimination, such as structural discrimination, impact of racial discrimination, and the cases of racial discrimination in Indonesia today.